The Effect of AI-Driven Personalization, Chatbot Interaction, and Dynamic Pricing on Consumer Purchase Decisions through Trust in AI Systems - Rizkyka Agsyana Amaretta; Alfatih Sikki Manggabarani (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The rapid adoption of Artificial Intelligence (AI) in digital marketing has changed how consumers interact with brands, particularly through personalized recommendations, chatbot services, and dynamic pricing. However, although these AI-based features are widely used on digital platforms, consumers may still question their reliability, fairness, and transparency. This study aims to examine the effects of AI-driven personalization, AI-enabled chatbot interaction, and AI-based dynamic pricing on consumer purchase decisions through trust in AI systems. This research employed a quantitative approach using a cross-sectional survey of consumers who had experience using AI-based features on digital platforms in Indonesia. Data was analyzed using PLS-SEM. The results show that AI-driven personalization and chatbot interaction positively influence purchase decisions, while dynamic pricing has no direct effect. Trust in AI systems significantly mediates the relationship between AI-based marketing features and purchase decisions. This study concludes that consumer trust is essential in converting AI-driven marketing strategies into purchase behavior.